ANALISIS KUALITAS PRODUK JORAN PANCING DENGAN MENGGUNAKAN METODE NEW SEVEN TOOLS - Daru Gilang Kristianto; Indro Prakoso (LPPM Universitas Bina Bangsa, 2023)
Today's industrial competition encourages companies to continue to improve the quality of their products. However, the quality of the product itself is not only influenced by how the processes occur in the production line, but also related to a series of flows starting from the arrival of materials until the product is received by consumers. As happened at PT. X, the company wants to identify product quality problems and reduce the number of product defects because many defective products are found. To control product quality, a method is used to reduce product defects by using the New Seven Tools method. New Seven Tools is one of the quality control methods used to find and solve qualitative problems. By using the New Seven Tools method, several causes of problems were found and recommendations for improvements were appropriate for each problem. Based on the results of the analysis to find the causes of quality problems using the New Seven Tools method, it can be concluded that there are 8 types of defects with 3 main factors causing defects, namely operator error during workmanship, poor material quality, and lack of quality inspection